A comparison of helminth infections as assessed through coprological analysis and adult worm burdens in a wild host. Issue 3 (December 2018) - Byrne, Rachel L.; Fogarty, Ursula; Mooney, Andrew; Marples, Nicola M.; Holland, Celia V.
Abstract: Coprological analysis is the most widely used diagnostic tool for helminth infection in both domestic and wild mammals. Evaluation of the efficacy of this technique is rare, due to the lack of availability of adult worm burden. Where information is available the majority of studies are in small ruminants and seldom in a wild host. This study of 289 wild badgers is the first to report the relationship between faecal egg/larval counts and adult worm burden in badgers whilst also evaluating the reliability of coprological analysis as a diagnostic tool for hookworm ( Uncinaria criniformis ) and lungworm ( Aelurostrongylus falciformis ) infection. The prevalence of hookworm and lungworm infection, as assessed through adult worm burden was 59.2% and 20.8% respectively. For both species of helminth, infection was consistently under-reported by coprological analysis compared to adult worm burden with a reported 41% sensitivity for hookworm and 10% for lungworm. A significant positive relationship was found between faecal counts and adult worm burden for both species of helminths. Additionally the density –dependent relationship often reported in helminth infection appears to be weak or non-existent in this study, up to the observed worm intensity of 500. Graphical abstract: Image 1 Highlights: Hookworm infection is endemic within the Irish badger population. Lungworm infection is also common in Irish badgers. Coprological analysis has a low sensitivity for diagnosing infection compared to adult worm burden. Faecal is a reliable indicator of intensity of infection. Density-dependence is weak, or non-existent up to the observed intensity of 500 worms.